Public Relations for the New Europe - Morris, Trevor. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2008)
This book is essential for anyone interested in Public Relations in New Europe Whether you are working in PR, studying PR, a journalist dealing with PR, or just interested in this fascinating and fast growing market, this book offers readers a vital insight into how PR works.